The Influence Of Social Media Towards Students Mood And Productivity In English Department Of Majalengka University - Asadelya Adora Rahma Putri; Yaniar Ratna Dewi (Papanda Publisher, 2025)
This study aims to analyze the extent to which social media usage affects the level of student learning productivity. This study will also identify specific factors in social media usage that have a significant impact on student productivity, such as platform type, duration of use, and content accessed. In addition, this study will examine how the use of social media as a learning tool can affect student learning outcomes.Using a case study approach, this study will explore students' experiences in using social media in the context of learning. Through an in-depth survey, researchers will collect qualitative data to better understand how students manage their time on social media, the types of content they consume, and its impact on their ability to focus on learning tasks.